Effects of moisture and fermentation length on the quality and digestibility of fermented concentrate using tamanu kernel cake as the main protein source through an in vitro study. - Paradhipta, Dimas Hand Vidya; Hanim, Chusnul; Agus, Ali; Leksono, Budi; Umroni, Aziz; Maharani, Sinta; Wardani, Arrynda Rachma Dyasti; Mukmila, Zazin (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The present study aimed to evaluate the effects of moisture and fermentation length on the chemical compositions, fermentation characteristics, feed-out phase, and ruminal digestibility of fermented concentrate using tamanu kernel cake (TKC) as the main protein source. Materials and Methods: The concentrate was formulated to contain 16.5% crude protein (CP) and 35% neutral detergent fiber consisting of 40% TKC, 7.60% soybean meal, 25.0% wheat pollard, 26.4% dried cassava, and 1% molasses. Those ingredients were mixed and fermented anaerobically at 5 kg into a vacuumed plastic bag with different additional sterile distilled water to reach moisture levels at 25% (MO25), 35% (MO35), and 45% (MO45). Each moisture level was incubated with different fermentation lengths consisting of 2, 7, 14, 21, and 42 days in quadruplicate. After fermentation, each silo was sub-sampled for laboratory analyses. Results: MO25 and MO35 led to higher CP with lower acid detergent fiber than MO45. In the fermentation, MO35 and MO45 generated higher (p < 0.05) lactate than MO25. An extended fermentation length linearly dropped (p < 0.05) dry matter, CP, and ether extract, but gradually increased (p < 0.05) ammonia-N, lactate, acetate, and the counts of lactic acid bacteria, yeast, and bacilli. After 42 days, MO25 and MO35 initiated higher (p < 0.05) aerobic stability. The digestibility and total volatile fatty acid (VFA) in the rumen increased (p < 0.05) over 2 days. However, prolonged fermentation length linearly decreased (p < 0.05) total VFA and methane emission without affecting rumen pH, ammonia-N, and each VFA profile. Conclusion: The application of MO35 was found to reduce nutrient loss and improve aerobic stability comparable to MO25 while achieving fermentation quality similar to MO45, and short-term fermentation, such as 2 days, could improve ruminal digestibility. J. Adv. Vet. Anim. Res., 12(2): 433–444, June 2025 http://doi.org/10.5455/javar.2025.l910